Enterobacteria isolated from an agricultural soil of Argentina promote plant growth and biocontrol activity of plant pathogens - López, Silvina Marianela Yanil (2019)
Bacteria promote growth by different mechanisms like phosphate (Pi) solubilization, Indol Acetic Acid (IAA) synthesis and siderophores production. The purpose of this study was to isolate bacteria that promote the growth of plants and may also act as antagonistic organisms of plant pathogens. Pi solubilizing microorganisms that were isolated from the soils of Tres Arroyos, Buenos Aires; were also able to synthesize IAA and produce siderophores. The ability of these bacteria to solubilize Pi was directly related with the synthesis of organic acids that lowered the pH and was not related with phosphatase activity. The ability of the organisms to solubilize Pi was indirectly related with the amount of soluble Pi present in the media. Though Pi solubilizing microorganisms are mainly associated with the rhizoplane exudates, in this case did not induce Pi solubilization. In addition to promote plant growth, these bacteria proved to be antagonistic of plant pathogens such as Fusarium graminearum and F. solani.